Contribution des paradigmes de l'intelligence artificielle pour la détection d'éventuels dommages au niveau des moteurs d'avion - Selmi nadine (university of eloued جامعة الوادي, 2024)
تعتبر الحالة الصحية لمحركات الطائرات ضرورية لضمان سلامة الرحلات الجوية. في الواقع، مع زيادة وقت الخدمة، تتعرض المكونات الداخلية للمحرك لتهديدات من مصادر مختلفة. لذلك، من الضروري اكتشاف الأضرار داخل المحرك بانتظام لتقليل تكاليف الصيانة. يمكن لتقنية التفتيش بالمنظار أن تشخص العيوب بنجاح وتوفر ضمانًا قويًا لأعمال الصيانة؛ ومع ذلك، فإن درجة الأتمتة والذكاء فيها منخفضة بشكل واضح. في هذا السياق، قمنا باقتراح إطار عمل أكثر تلقائية لاكتشاف عيوب محركات الطائرات بناءً على أحدث الأبحاث الحالية: التعلم العميق لاكتشاف عيوب محركات الطائرات من خلال مجموعة بيانات محلية. يتكون إطار العمل المقترح (YOLOv8) من ثلاث مراحل تغطي: جمع البيانات، تدريب النموذج، وتقييم النموذج. في الواقع، يمكن للنظام المقترح اكتشاف سبعة أنواع من الأضرار بدقة وكفاءة من صور المنظار الداخلي بما في ذلك: الشقوق، النقر، ارتفاع درجة الحرارة، تجعد الأطراف، التآكل، الاحتراق، والكسر بتحقيق دقة عالية. علاوة على ذلك، يكتسب القدرة على إخراج كل من المناطق وأنواع الأضرار داخل الصور المدخلة. أخيرًا، قمنا بالتحقق من صحة إطار العمل الخاص بنا على بيانات هندسية تم تنزيلها وحققنا نجاحًا في اكتشاف الأضرار. وبالتالي، تغلبنا على التحديات. يوفر إطار العمل المطور للتعلم العميق فائدتين مزدوجتين: تقليل الوقت المطلوب لأداء فحص المنظار الداخلي اليدوي لمحركات الطائرات وتحسين السلامة العامة بالنسبة لصناعة الطيران بعيدًا عن الأخطاء البشرية. لا يزال تطبيق التعلم العميق في مجال اكتشاف عيوب محركات الطائرات فيمراحله الأول The health condition of an aero-engines is pivotal to the safe flight mission of an aircraft. Indeed, with the increase of service time, the engine internal components will be affected by threats coming from different sources. Hence, it is necessary to detect the damage inside the engine regularly to decrease maintenance costs. Borescope inspection technology can successfully diagnose the fault and provide a strong guarantee for the maintenance work; however, its grade of automation and intelligence is clearly low. In this sense, we have proposed a more automated aero-engine defect detection framework based on the current research hot spot: deep learning for aero engine defect detection through a local dataset. The proposed YOLOv8 framework is 3-phases covering: data acquisition, model training and model evaluation. Indeed, the proposed system can accurately and efficiently detect seven types of damages from borescope images including: Crack, Nick, Overheated, Tip curl, Corrosion, Burned and Broken by reaching high accuracy. Furthermore, it gains the ability to output both the regions and the types of damages within input images. Finally, we validated our framework on downloaded engineering data and achieved successful damage detection. Hence, we overcome the challenges. The developed deep learning framework provides dual benefits of reducing the time required to perform otherwise manual aero-engine borescope inspection and improving the overall safety relative to the aerospace industry free from human error. Applying deep learning in the field of aero-engine defect detection is still in its infancy.
memouer master informatuique
Keywords: حرك طائرة، اكتشاف العيوب، التعلم العميق، صور المنظار الداخلي،YOLOv8، التجزئة، التصنيف; Aero-engine; defect detection; deep learning; Borescope images; YOLOv8; segmentation; classification.